Indium tin oxide-based Q-switched fiber laser generation and sensing application - Zalkepali @ Zulkefli, Noor Ummi Hazirah Hani (2021)
A pulsed fiber laser has gained significant attention due to widespread and useful photonics applications in the fields of high-speed communications, optical imaging, and material processing. Q-switching and mode-locking are two possible pulse fiber lasers that can be generated using active and passive techniques. The active technique requires a bulky and complex modulator, but the passive technique uses only a piece of a nanomaterial as a saturable absorber (SA) to induce loss modulation in laser configurations. In this regard, the active material of indium tin oxide (ITO) was used to build a SA device through DC magnetron sputtering in generation Q-switched pulse erbium-doped fiber laser (EDFL). ITO was never used for tuning wavelength with an intra-cavity filter and the application of pulse fiber laser such as a sensor. Two different implementation methods of ITO were successfully fabricated and characterized for Qswitching. The first ITO was deposited onto fiber ferrules to observe the performances of Q-switched pulse EDFL using various configurations such as linear, single ring, and Figure-8 cavities that have the repetition rate of 18.20 kHz, 38.03 kHz, and 24.19 kHz, respectively. Thus, the single ring configuration was selected and improved to enable Q-switched wavelength tunability by employing a tunable bandpass filter (TBF). The tunable Q-switched pulse EDFL wavelength was operated from 1540.0 nm to 1570.0 nm. The generated output pulses displayed a repetition rate of 94.34 kHz and the shortest pulse width of 3.22 µs at the maximum pump power of 378.6 mW. Next, the stable switchable dual wavelength was generated by the aid of two selected fiber Bragg gratings in the single ring cavity. To achieve a flexible switched in individual wavelength of 1532 or 1533 nm and a simultaneous dual-wavelength fiber laser, the in-line polarization controller had to be adjusted. The second device implemented onto the side-polished fiber, coated with ITO (SPF-ITO), had generated as a novel method for Q-switching and ammonia sensor. The SPF-ITO was successfully utilized as the SA as well as a sensor for monitoring different concentrations of the ammonia solution. The pulsed fiber laser ammonia sensor can be observed through the shifts in wavelength and frequency domain due to the interactions between the ammonia molecules and ITO thin film where the SPF-ITO was immersed in the ammonia solution. The shifts of wavelength from 1558.45 nm to 1554.25 nm resulted from the increase in ammonia concentrations from 0.5 x 105 to 3.0 x 105 ppm. The wavelength shifted from 1561.30 nm to 1559.35 nm using an increased concentration of ammonia from 1 to 10 ppm. Meanwhile, the shifts of RF signal from 35.50 kHz to 43.50 kHz were the result of the change in ammonia concentrations from 0.5 x 105 to 3.0 x 105 ppm. The RF signal shifted from 30.10 kHz to 33.70 kHz in tandem with the increase of ammonia concentrations from 1 to 10 ppm. In brief, the SPF-ITO was successfully fabricated for the Q-switcher as well as the sensor